Optimization of the Energy Performance in the Hospitality Sector in UAE by Using the Integrated Control Methodology in the Guestrooms - AlFaris, Fadi (2014)
This dissertation aims to study the energy efficiency in the hospitality sector in UAE. It will discuss the energy benchmarking analysis for the lodging buildings to differentiate between the usual practice and best practice in terms of energy performance for the hotels. This research focuses on developing several criteria such as; the hotel’s gross floor area, star classification, building age, occupancy rate, guestrooms number, construction code and regulation and cooling energy source, to appraise the hotel building energy consumption with, by gathering a real energy data and basic building information, normalization of energy use index and analyze these data statistically to ascertain the expected energy performance and consumption in UAE. About 19 hotel buildings energy data was analyzed to provide the energy benchmarking findings in UAE hotels. Besides, the normalized energy use index kWh/m²/year has been concluded for the best, usual and poor practice hotels. It was found after the analysis of the collected data that the normalized EUI ranges between lower than 241.5 kWh/m²/year as a best practice and greater than 361.3kWh/m²/year of the poor energy practice for the hotels constructed after the year of 2003, when more stringent code adopted by Dubai Municipality. Whereas the hotels’ energy data showed higher values for those constructed before 2003, as the normalized EUI varies between lower than 348.4 kWh/m²/year as best practice and greater than 511.1kWh/m²/year. As the hospitality sector in UAE is growing to meet the current and upcoming demand. It would be an important requirement to reduce the gap between the poor, usual and the best energy management practices. In this dissertation, the integrated control strategy for the guestroom has been studied and modeled to present the potential of energy savings that might be achieved by using such integrated techniques. The building energy model in hourly basis has been conducted to assess the energy performance improvement after adopting the proposed system. It shows that at least 31.5% might be improved out of entire energy consumption of the hotel including electricity and gas; 43.2% energy savings for the cooling system and 13.2% for lighting system of the guestroom by installing the integrated control system.